Effect of foam rolling on agility and flexibility among university-level athletes - Affendy, Ammar Rasyid; Sazali, Razif; Zulqarnain, Muhammad; Haziq, Amrun; Adnan, Aizzat; Linoby, Adam; Md Yusoff, Yusandra (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the acute impact of foam rolling on agility and flexibility among university-level athletes to clarify its practical value in athletic training. By examining immediate performance changes following a foam rolling intervention, the research aims to provide evidence-based insights that can inform the design of effective warm-up and recovery protocols. Ultimately, the findings seek to resolve existing ambiguities regarding the effectiveness of this widely used technique in enhancing neuromuscular readiness and joint range of motion.